Answers

2014-06-30T22:03:41+05:30
Here is the answer. sinA/1+cosA + 1+cosA/sinA = [sin^2A + (1 + cosA)^2]/sinA(1 + cosA) = (sin^2A + 1 + cos^2A + 2cosA)/sinA(1 + cosA) = (1 + 1 + 2cosA)/sinA(1 + cosA) [since,sin^2A + cos^2A = 1] = (2 + 2cosA)/sinA(1 + cosA) = 2(1 + cosA)/sinA(1 + cosA) = 2/sinA = 2 cosecA [since 1/sinA = cosecA] = R.H.S.
0
  • Brainly User
2014-07-01T09:55:24+05:30
= sinA/1+cosA + 1+cosA/sinA
= [sin^2A + (1 + cosA)^2]/sinA(1 + cosA)
= (sin^2A + 1 + cos^2A + 2cosA)/sinA(1 + cosA)
= (1 + 1 + 2cosA)/sinA(1 + cosA) [since,sin^2A + cos^2A = 1]
= (2 + 2cosA)/sinA(1 + cosA) = 2(1 + cosA)/sinA(1 + cosA)
= 2/sinA = 2 cosecA [since 1/sinA = cosecA] = R.H.S.

Proved
0
mark as best plzzzzzzzzzzzzzzzzzzzzzzzzzz